PERSEPSI KEPALA SEKOLAH TERHADAP KEMAMPUAN GURU DALAM MEMANFAATKAN MEDIA BERBASIS TEKNOLOGI INFORMASI DI GUGUS XXII SD GAROT ACEH BESAR - Agustina Dewi; M. Yamin; Intan Safiah (Universitas Syiah Kuala, 2023)
This study intends to explain the principal's response to the teacher's ability to utilize technology-based media. In this study the approach used is a type of qualitative approach. Through a descriptive research model. With so many research subjects, there were four school principals. As well as structured interviews with a total of twelve questions used as a data collection method. The steps of qualitative research data analysis were then applied to all the data collected, by presenting data, presenting data, and writing conclusions. Based on the results of questions and answers that have been conducted with school principals, the ability of teachers to utilize technology-based media in Cluster XXII (Garot Public Elementary School, Garot Geuceu Public Elementary School, Jeumpet 1 Public Elementary School and Jeumpet 2 Public Elementary School) is still relatively low. From the results of interviews with the four school principals it is known that one of the inhibiting factors in utilizing technology-based media is inadequate facilities in schools so that teachers have not used technology-based media to the fullest, apart from inadequate facilities, there are still many teachers who are unable to apply information technology-based media because they are not used to using it during the teaching and learning process in class.